RESPONS FISIOLOGIS DAN KETAHANAN PANAS KAMBING BOERAWA DAN PERANAKAN ETTAWA PADA MODIFIKASI IKLIM MIKRO KANDANG MELALUI PENGKABUTAN - Qisthon, Arif; Hartono, Madi (JURNAL ILMIAH PETERNAKAN TERPADU, 2019)
This research aimed to study the effect of microclimate modification of pensby misting and the goats breeds (Boer and Ettawa crossbreeds) on physiological responses to adapt to the hot environments. The study was conducted from August-September 2018 at the UPTD Goat Breeding Center, Lampung Plantation and Livestock Service Office located in Negeri Sakti, Pesawaran Regency. The study used a split plot design in completely randomized design. Two treatments were applied in this study, namely modification of the pen consisting of pens without misting and pens with misting and the goat breed namely Boerawa and Ettawa crossbreed (PE). Twelve female goats were used in this study, each of six Boerawa and PE respectively. The parameters observed were microclimate conditions, namely air temperature,relative humidity, and Temperature Humidity Index (THI) and physiological responses consisted of respiration rate, heart rate, rectal temperature, and Heat Tolerance Coefficient (HTC). The results showed that there was no effect of the interaction between the treatment of misting and the breeds of goat on respiration rate, heart rate, rectal temperature, and HTC. Misting can improve air temperature, THI, respiration rate and HTC, on the other hand, does not affect the heart rate and rectal temperature. Goat breed has no effect on all physiological responses. Thus, modification of the microclimate by misting effectively maintains body temperature under normal conditions and increases the adaptability of goats to hot environments. Keywords: Physiological Responses, Microclimate Conditions, Microclimate Modification, Misting